A comparative study and experimental validation on single phase series active power filter control strategies using pi, flc and sliding mode controllers - Abdallah Ben Abdelkader; Othmane Abdelkhalek; Ismail Khalil Bousserhane; Mohamed Amine Hartani; Aymen Omari (Institute of Advanced Engineering and Science, 2019)
Sensitive loads are widely used in industrial, which is the main cause of sag-swell and harmonics voltages problems that can affect the power quality. Among the devices that solve such power quality perturbations, the series active power Filter APFS is considered in this paper. Thus, a single phase APFS is developed through an analytic analysis, supported by an experimental validation, where we applied classical proportional integrator PI, fuzzy logic FLC and sliding mode SM controllers to improve the dynamic response of the APFS. In addition, a comparative study between these control strategies has made in order to mitigate voltage sag-swell and especially harmonics, where the SMC has showed more effective and robust results compared to PI and FLC and proved by the Total harmonic distortion THD ratio. Results of the proposed controllers are simulated in MATLAB simulink® and validated through experimental tests applied on our system prototype.